RELATIONSHIP OF OIL CONTENT WITH EPIPELIC DIATOMS ABUDANCE IN INTERTIDAL SEDIMENT IN THE WATER OF TANJUNG BUTON SIAK DISTRICT RIAU PROVINCE - Novi Permata Sari; Yusni Ikhwan Siregar; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
A study on the effect of oil content on the epipelic diatom abundance weredone in march 2016 at Tanjung Buton intertidal. Three station were estabelishedare three replicades in calloting water as well as sediment sample. The analysis,identification and quantification of oil content and diatom abundance were carriedout in Marine Chemistry Laboratory and Marine Biology Laboratory, Faculty ofFisheries and Marine Science, University of Riau in Pekanbaru. It showed that oilcontent large apparentle the highest station 2 (1.224,10 ppm) and the lowest wasat station 1 (150,30 ppm). The highest abundance epipelic diatom of was found atstation 3 (15.752,33 Ind/cm2) and the lowest abundance was found at station 2(8.893,09 Ind/cm2). Epipelic diatom that were found in the water around theTanjung Buton Siak District Riau Province composing of 19 spesies. Rhizosoleniasp was the species with the highest abundance in all station. The epipelic diatomabundance was found to be during at different zone was in upper zone (15.313,65Ind/cm2), middle zone (13.638,73 Ind/cm2) and lower zone (11.325,72 Ind/cm2).Relationships between oil content with epipelic diatom abundance in TanjungButon Waters were y = -3,963x + 15.486, R2 = 0,400, r = 0,632. The oil contentand epipelic diatom abundance was negative correlation, which means in creasingof oil content will cause a decrease the abundance of epipelic diatom at TanjungButon waters.Keywords: Tanjung Buton Waters, Oil Content, Epipelic Diatom, Rhizosolenia sp